Using open access observational data for conservation action: A case study for birds. (April 2017) - Sullivan, Brian L.; Phillips, Tina; Dayer, Ashley A.; Wood, Christopher L.; Farnsworth, Andrew; Iliff, Marshall J.; Davies, Ian J.; Wiggins, Andrea; Fink, Daniel; Hochachka, Wesley M.; Rodewald, Amanda D.; Rosenberg, Kenneth V.; et al.
Abstract: Ensuring that conservation decisions are informed by the best available data is a fundamental challenge in the face of rapid global environmental change. Too often, new science is not easily or quickly translated into conservation action. Traditional approaches to data collection and science delivery may be both inefficient and insufficient, as conservation practitioners need access to salient, credible, and legitimate data to take action. Open access data could serve as a tool to help bridge the gap between science and action, by providing conservation practitioners with access to relevant data in near real time. Broad-scale citizen-science data represent a fast-growing resource for open access databases, providing relevant and appropriately scaled data on organisms, much in the way autonomous sensors do so on the environment. Several such datasets are now broadly available, yet documentation of their application to conservation is rare. Here we use eBird, a project where individuals around the world submit data on bird distribution and abundance, as an example of how citizen-science data can be used to achieve tangible conservation science and action at local, regional, and global scales. Our examination illustrates how these data can be strategically applied to improve our understanding of spatial and temporal distributions of birds, the impacts of anthropogenic change on ecological systems, and creative conservation solutions to complex problems. We raise awareness of the types of conservation action now happening with citizen-science data, and discuss the benefits, limitations, and caveats of this approach. Highlights: We propose that open access data can help bridge the gap between science and action. We classify 159 conservation actions based on eBird data use into six categories. We show exemplars of how eBird data are used for conservation science and action.